Comparison of the Plaque Removal Efficacy of Aquajet Water Flosser and Dental Floss in Adults After a Single Use. (A PrelimiNary Study) - F Sarlati; A Azizi; N Zokaei; N Mohaghegh Dolatabadi; M Hasanzadegan Roudsari; AR Moradi Hajiabadi (Islamic Azad University, 2016)
Background and Aim: Toothbrushes cannot reach all interdental areas. Interdental cleaning is an important part of oral hygiene care. The purpose of this study was to compare the supragingival plaque removal efficacy of an interdental cleaning power device (Aquajet) and dental floss. Materials and Methods: Thirty subjects were enrolled in this single-blind, split mouth clinical trial. All the subjects received both written and verbal instructions and demonstrated proficiency prior to the study. The subjects were asked to abstain from oral hygiene methods for 48 hours prior to the study. The subjects were scored using the Proximal/Marginal Plaque Index (PMI). Then, the four oral quadrants were randomly assigned to one of two treatment groups: One upper and one lower quadrant: Aquajet and the other two quadrants: dental floss.  The subjects were observed to ensure that they have covered all areas and have followed the instructions. Afterwards, they were scored again using the PMI. The pre and post-cleaning plaque scores were evaluated using two-way repeated measure ANOVA. Results: Both Aquajet and dental floss showed significant reduction of the baseline PMI in all dental areas (P<0.05), but the difference between the groups was not significant (P>0.05). Aquajet was significantly more effective than dental floss in reducing plaque on the mesial, mid-buccal and distal surfaces of upper first premolar and on the mesial and distal surfaces of upper second premolar and first molar (P<0.05). Conclusion: The results proved that oral irrigation with Aquajet is as effective as that with dental floss in plaque removal, and that Aquajet had significantly higher plaque removal efficacy at hard-to-reach dental surfaces.